Пошаговое объяснение:
a*b= A
=
=(0;-15;0)
|A| = √A²x + A²y + A²z = √(0² + (-15)² + 0²) = √(0 + 225 + 0) = √225 = 15
cos α = Ax/IAI = 0/15 = 0
cos β = Ay/IAI = -15 / 15 = -1
cos Ф = Az/IAI = 0/15 = 0
Пошаговое объяснение:
a*b= A
=![=i (0*4 - (-1)*0) - j (3*4 - (-1)*3) + k (3*0 - 0*3) = i (0 - 0) - j (12 + 3) + k (0 - 0) =](/tpl/images/1508/6553/409fb.png)
=(0;-15;0)
|A| = √A²x + A²y + A²z = √(0² + (-15)² + 0²) = √(0 + 225 + 0) = √225 = 15
cos α = Ax/IAI = 0/15 = 0
cos β = Ay/IAI = -15 / 15 = -1
cos Ф = Az/IAI = 0/15 = 0